Gish Jen: Loosening the Canyon of the Canon - Mashchenko, Olena (Respectus Philologicus, 2016)
The idea of the article is to analyse the complicated interweaving of Chinese and Euro- Atlantic literary tradition in Gish Jen’s writings. Asian wing of American literature is a phenomenon that has declared its existence comparatively not long ago. The voice of Asian American writers was initially not very loud. However, at the turn of 20th-21st centuries contours of American literature began to change due to the influence of a new concept of man and world arisen in the writings of Maxine Hong Kingston, Tamezo Mori, Amy Tan, Kazuo Ishiguro, Gish Jen.On the one hand, G. Jen’s texts are written by the canons of a postmodern narrative, which implies the poetics of decentration and fragmentation of the text, irony, double code, multi-layered intertextuality. Sternian satirical dispute with literary and scientific works of his time, inherited by postmodern writers, has become one of the brightest distinctive characteristic of G. Jen’s texts as well. Like other postmodern writers, she creates literary and intellectual fabric of the text into which responses to a variety of influential theories and concepts of the turn of 20th-21st centuries are interwoven. On the other hand, the writer develops the tradition of Asian literature with its emphasis on moral and spiritual existence of a man. This tradition sees a man not as a battlefield but an interplay of good and evil. This interplay may not make a man perfect, but it makes him human.